Perbedaan Karakter Clifford Geertz Dan Snouk Hurgonye: Telaah Perspektif Edward Said - Hanifa Maulidia (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2023)
This paper aims to explain the differences between Clifford Geertz and Snouk Hurgonye in Edward Said's perspective. The research method in this paper is using literature studies from several sources, namely Said's writings entitled Orientalism, articles and books discussing postcolonialism, Edward Said, Clifford Geertz and Snouk Hurgonye. The conclusion is that both of them were Westerners, who researched Indonesian society, religion, and culture. If Geertz researched Religion in Java, especially Islam, Hurgronye researched Islam in Aceh. Said showed his preference for Geertz in carrying out the research process. Because the writings and activities they carry out imply that it is purely research, no Hurgronye is an orientalist in which it is related to the relationship and distinction of citizenship (difference civilization) between the west (occcident) and the east (orient) which contains political elements, domination over west as superior and east as inferior, and complex hegemony and not pure research. Meanwhile, Geertz was not an orientalist, but was purely an academic or scientist who was researching and observing the area and society he was researching at that time.